Optimizing Local Corn Cultivation Systems on Kisar Island, South West Of Mollucas - Taihuttu, Hermina Neltje; Polnaya, Fransin; Marasabessy, Dessy Ariyani (Jurnal Agrohut, 2025)
Corn (Zea mays L) is a substitute for rice crops in food diversification program, the raw materials of food industry, beverages, and feed. Corn contains carbohydrates, protein, fat, vitamins and fiber. Kisar Island in Maluku district southwest of corn is a staple food source. Corn is usually consumed as boiled, grilled, fried, as a raw material for making cakes. Kisar Island is one of the islands in Maluku province that people cultivate corn crops in conventional farming systems. This study aims to determine the system of local corn cultivation in Kisar Island South West Maluku district. Research conducted in Kisar Island in Mei until August 2023. This study used purposive sampling method wich is survey and interview. The survey was conducted to determine the system of local corn cultivation in Kisar Island. Interviews were conducted to farmers as respondents . The results showed: 1. Local corn plants on the island of Kisar were cultivated around the house or yard, 2. Local corn cultivation system in Kisar Island has been done traditionally for generations, 3. Local corn cultivation in Kisar Island is done because it brings benefit socially, economically and ecologically.